Pengaruh Manajemen Keuangan terhadap Kinerja Perusahaan : Studi pada UMKM di Era Digital : Literature Review - Adeliya Adeliya; Yohana Putri; Rudi Sanjaya (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2025)
Financial management is one of the key factors in determining the success of a company, especially for Micro, Small, and Medium Enterprises (MSMEs) in the digital era. This study aims to analyze the literature that discusses the influence of financial management practices on MSME performance, considering the role of digital technology in financial management. This study explores key aspects of financial management, such as financial planning, budget control, cash flow management, and investment, and how the application of technology can improve its efficiency and effectiveness. The results of the study show that the use of digital technology, such as cloud-based accounting applications and digital payment systems, can improve the accuracy and speed of financial management, which ultimately has a positive impact on MSME performance. This study provides important insights for MSME actors and policy makers in integrating digital technology to strengthen financial management and improve business competitiveness.